Anorexia nervosa with fatal outcome: A case report - Aliaga-Tinoco, Stephanie (2020)
Anorexia Nervosa (AN) is the psychiatric disorder with the highest direct mortality level and, at the same time, the cause of multiple and risky somatic complications such as bradycardia, orthostatic hypotension, cardiac arrhythmias, hypoglycemia, liver failure, hydro-electrolytic and hormonal disorders, osteopenia, gastric dilation and, finally, sudden death from different causes. Despite its relatively low prevalence, it affects young people with a long life expectancy. Its medical management, when reaching a high severity level (BMI <15), is complex as it requires joint work between psychiatry and other medical specialties, and can even have ominous consequences. The case of a 19-year-old woman whose BMI was around 11, and who unfortunately died while receiving hospital care, is discussed. The main complications of AN are reviewed, and the need to consider the relevant parameters for a timely hospital care are highlighted, in order to avoid fatal outcomes.